Safety and efficacy of twice daily administration of KPI-121 1% for ocular inflammation and pain following cataract surgery - Kim T (Dove Medical Press, 2018)
Terry Kim,1 Kenneth Sall,2 Edward J Holland,3 R Kim Brazzell,4 Susan Coultas,4 Preeya K Gupta1 1Department of Ophthalmology, Duke University Eye Center, Durham, NC, USA; 2Sall Research Medical Center, Inc, Artesia, CA, USA; 3Department of Ophthalmology, Cincinnati Eye Institute, University of Cincinnati, Cincinnati, OH, USA; 4Kala Pharmaceuticals, Inc, Waltham, MA, USA Purpose: KPI-121 is a nanoparticle suspension of loteprednol etabonate with improved ocular pharmacokinetics compared with marketed formulations. The efficacy and safety of KPI-121 1% ophthalmic suspension (INVELTYS™) dosed twice daily (BID) were evaluated in participants who had undergone cataract surgery. Materials and methods: In two multicenter, randomized, double-masked, parallel-group, vehicle-controlled clinical trials, 386 participants with ≥ grade 2 anterior chamber cells (≥6 cells) on the day following routine cataract surgery were treated with KPI-121 1% and 325 participants were treated with placebo (vehicle); each group was dosed BID for 2 weeks. Primary efficacy endpoints were complete resolution of ocular inflammation by slit-lamp biomicroscopy and complete resolution of subject-rated ocular pain at Days 8 and 15 with no rescue medication before Day 15. Safety assessments included adverse events (AEs), visual acuity, intraocular pressure measurements, and evaluation of ocular AEs by slit-lamp biomicroscopy and dilated ophthalmoscopy. Results: Both trials achieved statistical significance favoring KPI-121 1% BID for both primary efficacy endpoints. Combined data analysis showed that significantly more participants treated with KPI-121 vs vehicle achieved complete resolution of anterior chamber cells at Days 8 and 15 (P≤0.0001) and complete clearing of ocular pain at Days 4, 8, and 15 (P<0.0001). AEs were reported more frequently with vehicle than KPI-121. Conclusion: KPI-121 1% ophthalmic suspension was effective in resolving postoperative ocular inflammation and pain when dosed BID for 2 weeks in patients following cataract surgery. KPI-121 was found to be safe and well tolerated in both trials. Keywords: loteprednol etabonate, nanoparticle, mucus penetrating particles, postoperative ocular inflammation, pain